Performing disunion the coming of the Civil War in Charleston, South Carolina - McDonnell, Lawrence T. (Cambridge studies on the American South, 2018)
This book traces how and why the secession of the South during the American Civil War was accomplished at ground level through the actions of ordinary men. Adopting a micro-historical approach, Lawrence T. McDonnell works to connect small events in new ways - he places one company of the secessionist Minutemen in historical context, exploring the political and cultural dynamics of their choices. Every chapter presents little-known characters whose lives and decisions were crucial to the history of Southern disunion. McDonnell asks readers to consider the past with fresh eyes, analyzing the structure and dynamics of social networks and social movements. He presents the dissolution of the Union through new events, actors, issues, and ideas, illuminating the social contradictions that cast the South's most conservative city as the radical heart of Dixie